2013
DOI: 10.1177/0003319713507332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Remote Ischemic Preconditioning in the Elderly Patients With Coronary Artery Disease With Diabetes Mellitus Undergoing Elective Drug-Eluting Stent Implantation

Abstract: There is conflicting evidence regarding the effectiveness of remote ischemic preconditioning (RIPC) in patients undergoing elective percutaneous coronary intervention (PCI). Therefore, we prospectively enrolled elderly patients with coronary heart disease (CHD) with diabetes mellitus (DM) undergoing elective drug-eluting stent (DES) implantation. They were randomized to receive RIPC within 2 hours before PCI (n = 102) or not (controls, n = 98). Baseline clinical characteristics were similar between the 2 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 41 publications
0
44
1
Order By: Relevance
“…A retrospective analysis of the CONDI trial (Effect of Remote Ischemic Conditioning on Clinical Outcome in (Table 3). A similar pattern with infarct size reduction in the majority but not all studies (with 2 small extreme outlier studies reporting even increased infarct size by remote ischemic preconditioning 114,115 ) emerged for elective PCI when either remote ischemic pre- [116][117][118][119][120][121][122][123] or postconditioning 124,125 was used for cardioprotection. In some of these studies, clinical outcome was reported as a secondary outcome, and it was either not different 106,119,124 or improved.…”
Section: Remote Ischemic Conditioningmentioning
confidence: 66%
“…A retrospective analysis of the CONDI trial (Effect of Remote Ischemic Conditioning on Clinical Outcome in (Table 3). A similar pattern with infarct size reduction in the majority but not all studies (with 2 small extreme outlier studies reporting even increased infarct size by remote ischemic preconditioning 114,115 ) emerged for elective PCI when either remote ischemic pre- [116][117][118][119][120][121][122][123] or postconditioning 124,125 was used for cardioprotection. In some of these studies, clinical outcome was reported as a secondary outcome, and it was either not different 106,119,124 or improved.…”
Section: Remote Ischemic Conditioningmentioning
confidence: 66%
“…However, it is difficult to distinguish the effect of diabetes from that of age on the remote ischemic preconditioning protocol. Furthermore, the authors of this study did not demonstrate that their remote ischemic preconditioning protocol was effective in a younger nondiabetic population (Xu et al, 2014). In an intriguing clinical study by Jensen et al (2012) it was reported that diabetic patients with a peripheral neuropathy failed to produce a cardioprotective humoral factor in response to a standard remote ischemic preconditioning protocol (4 Â 5-minute upper arm cuff inflation/deflation) compared with nondiabetic and diabetic patients who did not have a peripheral neuropathy.…”
Section: Diabetesmentioning
confidence: 72%
“…Although many of these clinical studies included diabetic patients they did not specifically address the question of whether the diabetic heart was amenable to remote ischemic conditioning. Xu et al (2014) found that a standard remote ischemic conditioning stimulus (3 Â 5-minute upper arm cuff inflations/deflation) did not reduce the magnitude or incidence of periprocedural myocardial injury during elective PCI in older patients (mean age 69 years) with diabetes. However, it is difficult to distinguish the effect of diabetes from that of age on the remote ischemic preconditioning protocol.…”
Section: Diabetesmentioning
confidence: 88%
“…With the exception that the percentage of patients with diabetes was lower in the study of Zografos et al , the sample size and study population were similar in both studies (21% vs. 31%). The presence of DM could attenuate the protective effects of RIPC [30]. The diabetic group in our study constituted about one third of the study population, without a significant difference between groups.…”
Section: Discussionmentioning
confidence: 94%
“…Although RIPC has promising effects, there are limited data about its effects in planned PCI. Different protocols, to test the possible protective effects of RIPC, were chosen in the previous studies [7, 12, 2530]. The study by Iliodromitis et al .…”
Section: Discussionmentioning
confidence: 99%